TRANSFORMASI DIGITAL DAN PERUBAHAN PERAN AKUNTAN DI ERA MODERN: A SYSTEMATIC LITERATURE REVIEW DENGAN PENDEKATAN PRISMA - Endah Arum Wangi; Asrie Dyah; Mildazani; Alfiany alim Imro'ah; Sheilla Amanda Putri; Sriayu Saputri Situmeang (UM. Bengkulu, 2026)
Technological advances are radically changing accounting. Yet, there is no integrated overview of how digital tools impact accountants’ roles and competencies. Objectives: This study provides a systematic review of literature (SLR/PRISMA) on digital transformation in accounting (2019–2025), synthesizing trends and identifying research gaps. Methods: Using PRISMA guidelines, 42 relevant Scopus-indexed articles were analyzed to extract insights on technologies (AI, big data, cloud, fintech, etc.), effects on accounting processes, and implications for the profession. Results: The analysis shows that automation and analytics enhance efficiency (reducing manual work) and elevate accountants into strategic advisors and data analysts. Key findings include the emergence of the “augmented accountant” concept, the crucial role of new competencies (data literacy, IT skills, critical thinking), and heightened stakeholder demands for real-time, transparent reporting. However, studies also note challenges: skill gaps in graduates, organizational resistance, and data security concerns. Conclusions: Digital transformation substantially redefines accounting practice. The review highlights theoretical contributions (integrative frameworks of technology and accounting roles) and practical implications (curriculum redesign, workforce upskilling). We outline clear future research directions, such as empirical validation of the proposed framework across diverse contexts and exploration of under-studied areas (e.g., blockchain’s impact, ethical considerations).